2014
DOI: 10.1136/bmjopen-2014-005097
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and short-term outcomes in patients with elevated admission systolic blood pressure after acute ST-elevation myocardial infarction: a population-based study

Abstract: ObjectivePrognostic value of lower admission systolic blood pressure (SBP) in patients with acute myocardial infarction has been confirmed, but the impact of elevated admission SBP on short-term outcomes has been evaluated only by a limited number of studies and they have reported conflicting results. The aim of our study was to investigate the characteristics and short-term outcomes in patients with elevated admission SBP after ST-elevation myocardial infarction (STEMI).DesignA population-based, observational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Hypertension was also not found to be significantly associated with the presence of MACE during the treatment of STEMI patients undergoing PPCI. Similar results were found by Huang et al 26 , with no significant difference in the occurrence of MACE during treatment in STEMI patients. The use of antihypertensive drugs such as angiotensin converting-enzyme blockers and beta blockers in the adequate management of STEMI can be cardioprotective for the occurrence of MACE.…”
Section: Discussionsupporting
confidence: 90%
“…Hypertension was also not found to be significantly associated with the presence of MACE during the treatment of STEMI patients undergoing PPCI. Similar results were found by Huang et al 26 , with no significant difference in the occurrence of MACE during treatment in STEMI patients. The use of antihypertensive drugs such as angiotensin converting-enzyme blockers and beta blockers in the adequate management of STEMI can be cardioprotective for the occurrence of MACE.…”
Section: Discussionsupporting
confidence: 90%
“…The initial blood pressure value registered during an acute coronary event is not necessarily representative of the baseline patient’s blood pressure control. Furthermore, the prognostic value of high systolic blood pressure values at admission in the setting of an acute STEMI remains controversial [ 29 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that ACS mortality is strongly related to admission BP with a J-shaped or U-shaped curve association, with the lowest adverse event rates in the SBP range of 130-140 mmHg and DBP range of 80-90 mmHg [8]. A large study showed that elevated admission SBP in patients with ST-segment elevation myocardial infarction (STEMI) was not associated with worse outcomes [9]. We assumed that preexisting hypertension might be protective in ACS patients in the short term despite its clearly established role in increasing the long-term risk for coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%